A Spherically Symmetric Model for the Tumor Growth - Saeed M. Ali; Ashfaque H. Bokhari; M. Yousuf; F. D. Zaman (Journal of Applied Mathematics)
The nonlinear tumor equation in spherical coordinates assuming that both the diffusivity and the killing rate are functions of concentration of tumor cell is studied. A complete classification with regard to the diffusivity and net killing rate is obtained using Lie symmetry analysis. The reduction of the nonlinear governing equation is carried out in some interesting cases and exact solutions are obtained.